2009
DOI: 10.1021/la901811g
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Assemblies of Molecularly-Linked Metal Nanoparticles and Multifunctional Properties

Abstract: The use of metal nanoparticles as building blocks toward thin film assembly creates intriguing opportunities for exploring multifunctional properties. Such an exploration requires the ability to engineer the size, shape, composition, and especially interparticle properties in nanoparticle assemblies for harnessing the collective properties of the nanoscale building blocks. This article highlights some of the important findings of our investigations of thin film assemblies of molecularly linked nanoparticles fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 202 publications
(229 reference statements)
1
75
0
Order By: Relevance
“…The exploration of nanostructured copper-based materials as building blocks towards multifunctional materials with technological applications requires, among others, their incorporation in a solid-state phase, usually as thin films [10]. Thus the preparation methods for nanostructured materials in their solid-state phase are of great importance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exploration of nanostructured copper-based materials as building blocks towards multifunctional materials with technological applications requires, among others, their incorporation in a solid-state phase, usually as thin films [10]. Thus the preparation methods for nanostructured materials in their solid-state phase are of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the preparation methods for nanostructured materials in their solid-state phase are of great importance. Specifically for copper oxides, solid-state preparation methods have been reported [6,7,[10][11][12][13][14][15][16]. Xu et al [7] prepared CuO nanocrystals by a one-step solid-state reaction of CuCl 2 ⋅2H 2 O and NaOH, while Kawahashi and Shiho [6] obtained hollow spheres by calcination of a polymer-coated Cu(NO 3 ) 2 salt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlling interparticle proximity by changing the length of DNA linkers allows for elaborate monolayer construction such as sheets with evenly spaced wells. 25 These monolayers can also be stacked and arranged in alternating molecular patterns through layerby-layer deposition. [26][27][28] Another means that may be amenable for attaching macromolecular DNA or RNA is by coating the gold surface with alternating layers of cationic and anionic polyelectrolytes.…”
mentioning
confidence: 99%
“…[7][8][9] It is often reported that the chemical properties of the stabilizers can be enhanced through interaction with the core metallic materials during optical and electrical analysis. [10,11] Since the stabilizers are usually bio-hazardous chemicals that are used to confine core materials' size and shape restriction, they would provoke unexpected side effects. Thus, a great effort has been made to synthesize biologically inert/compatible NPs.…”
Section: Introductionmentioning
confidence: 99%